First records of Anthopleura nigrescens (Verrill, 1928) and Telmatactis panamensis (Verrill, 1869) (Cnidaria, Anthozoa, Actiniaria) from Parque Nacional Coiba, Pacific coast of Panama - Fabián H. Acuña; Ricardo González-Muñoz; Agustin Garese; Edgardo Díaz-Ferguson (Check List, 2022)
We report two species of sea anemones, Anthopleura nigrescens (Verrill, 1928) and Telmatactis panamensis (Verrill, 1869), for the first time from Parque Nacional Coiba, a large, protected area in the Pacific off Panama. In addition, we describe the external anatomical taxonomic characters and provide images of live specimens of each species. The number of sea anemones species known for Panama is updated to 57. This work constitutes the first study in the documentation of sea anemones of Coiba Island.